Standardized Assessment and Examination in Islamic Religious Education - Siti Rosyidah; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education is very important for human life so it must be fulfilled and carried out to improve the quality of human life. Therefore, to see the results or progress of this education, evaluation and assessment are needed to be a benchmark for whether the education is getting good or bad results. Evaluation and assessment must be carried out by an educational institution, but this evaluation and assessment has an administration that must be followed by an educational institution. This article explains clearly the administration of evaluation and assessment in education including definitions, objectives, functions, scope and targets.